Assessing readiness on blended learning among lecturers in Universiti Teknologi MARA (Perlis) / Nurul Anis Awang Ali - Awang Ali, Nurul Anis (2014)
Blended learning, involves the combination of two fields of concern: technology and education; or two groups of people: technologists and educationists. However, the readiness of lecturers in using or assessing a blended learning is very important in applying this to their students. This study aimed to investigate the extent to which the lecturers of UiTM are ready on the blended learning. This study also include to identify the factors those affect the readiness among lecturers on blended learning. The research is reflected in 4 questions: (I) Is the appropriate technology for blended learning is available? (2) Has lecturers shows their confidence in using technology that provided by institution? (3) What are the factors that affect readiness on blended learning among lecturers? (4) Is teaching experience will affect the readiness of using blended learning in lectures? The lecturers were given questionnaires and were interviewed in order to determine their experiences in the Blended Learning environment. The findings indicate whether the lecturers totally ready or not with the blended learning. I used a blended learning model which include people, technology, institution and content that indicates the boundary of the current literature and research findings, and a blended learning definition an educational-focused process to enhance and transform face to face learning with the blend of technology in a symbiotic relationship The wide use of online technologies and internet in the field of education and the opportunity of blending face-to-face instruction with online teaching environments foreshadow a shift in the way of delivering instruction to the learners as well. The analysis shows that lecturers mostly are ready on assessing a blended learning in UiTM.